The Managing Director's Global Policy Agenda. (Policy Papers; Policy Paper ;, 2016)
Full text also available in Arabic, Chinese, French, Japanese, Russian, and Spanish. Despite signs of recovery and resilience in some economies, global growth continues to disappoint, with the expected pick-up driven primarily by emerging markets. This persistent underperformance has exposed complex underlying trends in many countries-including the difficulty for some groups to adjust to rapid changes in the global economy. Policymakers should act and use a balanced mix of all policy levers to revive demand and raise productivity, and ensure the gains from technology and globalization-which have led to unprecedented global welfare gains in recent decades-are shared more broadly. A retreat from globalization and multilateralism is a serious risk at a time when international cooperation and coordination are as critical as ever. The Fund can assist by helping policymakers in their efforts by providing advice, developing capacity, and lending to countries in need, while continuing to advocate for multilateral solutions that work for all.